A community‐based, cross‐sectional study of hrHPV DNA self‐sampling‐based cervical cancer screening in rural Karnataka, India. Issue 2 (30th May 2019) - Adsul, Prajakta; Srinivas, Vijaya; Gowda, Savitha; Nayaka, Shivamma; Pramathesh, Rashmi; Chandrappa, Kavitha; Khan, Anisa; Jayakrishna, Poornima; Madhivanan, Purnima
Abstract: Objective: To examine the feasibility of implementing a high‐risk HPV (hrHPV) DNA‐based screening program for cervical cancer and the prevalence of hrHPV DNA‐positive women in a community setting in rural India. Methods: A cross‐sectional study was conducted at the community level in the Hunsur taluk of the Mysore district from January to August 2016. Cervical cancer screening was conducted with self‐collected vaginal samples that were analyzed using the Hybrid Capture 2 (HC2) assay (Qiagen, USA). Results: The majority of participants were aged 30–39 years, with no formal schooling, from a lower caste, and lived below an annual household income of US1499. After group health education and one‐on‐one counseling, a total of 473 women underwent self‐sampling. Of these, 36 (7.6%) were positive for hrHPV and only 24 (66.6%) underwent follow‐up diagnostic triaging. Cancer was detected in two women, who were referred to appropriate healthcare facilities for further treatment. Conclusion: Implementation of hrHPV DNA‐based screening tests using self‐sampling can be feasible in rural settings in India. However, substantial resources are required for providing health education and one‐on‐one counseling to inform asymptomatic women about the benefits of testing and, more importantly, to improve compliance with follow‐up. Abstract : Cervical cancer screening using HPV DNA tests with the option for self‐sampling can be implemented in medically underserved communities in India to improve access.